Propuesta de diseño del sistema de gestión de seguridad y salud en el trabajo (Sg-Sst) bajo la norma ISO 45001:2018 en la empresa YJS Construcciones SAS de Cartagena (2022)
The main purpose of this project is to provide a proposal for the design of the Occupational Health and Safety Management System (SG-SST), under the ISO 45001:2018 standard, applied in the company YJS Construcciones S.A.S., with the only headquarters located in the city of Cartagena de India. focusing the occupational health and safety management system on the activities of low and medium voltage electrical installations, for the prevention, surveillance and control of risk factors that may arise at the time of exercising this high-risk activity, due to the manipulation of electrical energies, creating an organizational culture of safety for workers, for an adequate identification of hazards in the work area, through procedures, programs and training to minimize the chances of accidents and absenteeism in the company and optimize the operational processes of YJS CONSTRUCCIONES S.A.S. thus obtaining socio-economic benefits.